2014
DOI: 10.1002/mrm.25396
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the microvessel caliber and density: Principles and applications of microvascular MRI

Abstract: Twenty years ago, theoretical developments were initiated to model the behavior of the NMR transverse relaxation rates in presence of vessels. These developments enabled the MRIbased mapping of mean vessel diameter, microvascular density, and vessel size index with comparable results to those obtained by a pathologist. The transfer of these techniques to routine clinical use has been hindered by the unavailability of the required sequences, namely fast gradient-echo spin-echo sequences. Based on the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 99 publications
2
67
0
Order By: Relevance
“…To reflect this complexity, we modeled tissue structures using ellipsoids (cells) (22, 23, 35) packed around randomly oriented cylinders (vessels) (36-45). Previously, we showed that modeling cells as ellipsoids rather than spheres provides a more accurate estimate of the magnitude of normalT2 changes observed in clinical DSC-MRI studies (22, 23, 35), whereas modeling the vasculature structure as randomly oriented cylinders has been shown to accurately estimate the normalT2 effects that occur when CA is distributed within blood vessels (36-45). The cylindrical vascular volume fraction was fixed using the in vivo extracted CBV values, and vessel sizes varied from 5 to 30 μ m (46).…”
Section: Methodsmentioning
confidence: 99%
“…To reflect this complexity, we modeled tissue structures using ellipsoids (cells) (22, 23, 35) packed around randomly oriented cylinders (vessels) (36-45). Previously, we showed that modeling cells as ellipsoids rather than spheres provides a more accurate estimate of the magnitude of normalT2 changes observed in clinical DSC-MRI studies (22, 23, 35), whereas modeling the vasculature structure as randomly oriented cylinders has been shown to accurately estimate the normalT2 effects that occur when CA is distributed within blood vessels (36-45). The cylindrical vascular volume fraction was fixed using the in vivo extracted CBV values, and vessel sizes varied from 5 to 30 μ m (46).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, for instance, a quantitative estimate of the vessel size can be obtained in a range between 10 and 200 lm for several brain tumors. 13 Calculation of the vessel size index, or mean vessel diameter, or vessel caliber index was performed and validated by functional and posttreatment measurements, and by histology in several animal studies ( [18][19][20][21][22][23][24][25] ; see also 26 for a review).…”
mentioning
confidence: 99%
“…Beyond rCBV mapping, USPIOs have been used to image the tumor microvasculature with MR-based assessment of the mean vessel diameter, microvascular density and vessel size index (VSI) [119,120]. This is important as the formation and development of vessels in cancers play a significant role in their progression and in their response to antitumor therapy [119].…”
Section: Imaging Treatment Effects and Therapy Monitoringmentioning
confidence: 99%